Mechanism of Action of 2-Aminobenzamide HDAC Inhibitors in Reversing Gene Silencing in Friedreich’s Ataxia - Soragni, Elisabetta; Chou, C. James; Rusche, James R.; Gottesfeld, Joel M. (Frontiers in Neurology, 2015)
The genetic defect in Friedreich’s ataxia (FRDA) is the hyperexpansion of a GAA•TTC triplet in the first intron of the FXN gene, encoding the essential mitochondrial protein frataxin. Histone posttranslational modifications near the expanded repeats are consistent with heterochromatin formation and consequent FXN gene silencing. Using a newly developed human neuronal cell model, derived from patient induced pluripotent stem cells, we find that 2-aminobenzamide histone deacetylase (HDAC) inhibitors increase FXN mRNA levels and frataxin protein in FRDA neuronal cells. However, only compounds targeting the class I HDACs 1 and 3 are active in increasing FXN mRNA in these cells. Structural analogs of the active HDAC inhibitors that selectively target either HDAC1 or HDAC3 do not show similar increases in FXN mRNA levels. To understand the mechanism of action of these compounds, we probed the kinetic properties of the active and inactive inhibitors, and found that only compounds that target HDACs 1 and 3 exhibited a slow-on/slow-off mechanism of action for the HDAC enzymes. HDAC1- and HDAC3- selective compounds did not show this activity. Using siRNA methods in the FRDA neuronal cells, we show increases in FXN mRNA upon silencing of either HDACs 1 or 3, suggesting the possibility that inhibition of each of these class I HDACs is necessary for activation of FXN mRNA synthesis, as there appears to be redundancy in the silencing mechanism caused by the GAA•TTC repeats. Moreover, inhibitors must have a long residence time on their target enzymes for this activity. By interrogating microarray data from neuronal cells treated with inhibitors of different specificity, we selected two genes encoding histone macroH2A (H2AFY2) and Polycomb group ring finger 2 (PCGF2) that were specifically down-regulated by the inhibitors targeting HDACs1 and 3 versus the more selective inhibitors for further investigation. Both genes are involved in transcriptional repression and we speculate thei